Job Satisfaction Study in Public and Private Sector Banks in Rajasthan: A Comparative Analysis between Public and Private Sector Banks in Rajasthan (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Job satisfaction is a significant issue which influences Industrial Psychology and behaviourmanagement. Job satisfaction is very important for motivation of employees and have positive attitudetowards one's job. Job satisfaction is related with factors like wages, supervision, conditions of work,social relation at workplace, quick solution of complaints, equal and fair treatment of employer. Jobsatisfaction is also affected with other factors like age, sex, education. The study theory revealed thatincreased job satisfaction leads to increase productivity, best achievements of goals and motivation. Thepresent research paper is an attempt to study the impact of job satisfaction among public and privatesector banks in Rajasthan. The quest of the research was to find out the relationship between jobsatisfaction in banking industry and correlate the different variables with the job satisfaction betweenpublic and private sector banks in Rajasthan.